A Case of Erythrodermic Psoriasis Successfully Treated with Risankizumab [Corrigendum] - Megna M; Ruggiero A; Salsano A; Lauletta G; Portarapillo A; Torta G; Martora F; Potestio L (Dove Medical Press, 2024)
Megna M, Ruggiero A, Salsano A, et al. Clin Cosmet Investig Dermatol. 2023;16:3503–3507. The authors have advised that the study did not receive any funding. The funding statement “Medical writing was funded through a donation by Abbvie Srl” on page 3506 should be removed. The authors apologize for this error.